2002
DOI: 10.1080/00343400220122089
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Clustering of Science and Capital: Accounting for Biotech Firm-Venture Capital Relationships

Abstract: This paper focuses on the spatial concentration of two essential factors of production in the commercial field of biotechnology: ideas and money. The location of both research-intensive biotech firms and the venture capital firms that fund biotech is highly clustered in a handful of key U.S. regions. The commercialization of a new medicine and the financing of a high-risk startup firm are both activities that have an identifiable timeline, and often involve collaboration with multiple participants. The importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
202
0
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(221 citation statements)
references
References 42 publications
6
202
0
13
Order By: Relevance
“…This hypothesized importance of spatial proximity has been supported by different international empirical studies, arguing that VC companies predominantly invest in nearby targets (Powell et al, 2002;Sorenson and Stuart, 2001;Cumming and Johan, 2006).…”
Section: Venture Capital As Driver Of Regional Developmentmentioning
confidence: 65%
“…This hypothesized importance of spatial proximity has been supported by different international empirical studies, arguing that VC companies predominantly invest in nearby targets (Powell et al, 2002;Sorenson and Stuart, 2001;Cumming and Johan, 2006).…”
Section: Venture Capital As Driver Of Regional Developmentmentioning
confidence: 65%
“…The role of venture capitalists in the regional innovation… network is also more readily tapped into when firms are geographically proximate (Powell et al 2002).…”
Section: Cost Theory and Geographical Proximitymentioning
confidence: 99%
“…Previous work by Powell et al (2002) examine the spatial concentration of ideas and money in the biotech sector and found that both research-intensive biotech firms and venture capital firms that fund biotech are highly clustered in a handful of key US regions. They also argue that the importance of tacit knowledge, face-to-face contact and the ability to learn and manage across multiple projects are critical reasons for the continuing importance of geographic propinquity in biotech.…”
Section: Cost Theory and Geographical Proximitymentioning
confidence: 99%
See 1 more Smart Citation
“…• In relation to exploitation-equity-based syndication conducted by investors may be mobilised by incubator management, strategic partnering, joint ventures of a technological nature and connections to consultants, specialist lawyers and IPR advisers and management accountants for business ''engineering'' will be supplied in-house or through the social capital networks that accrue to bioincubators and constitutes their key management resource of value along with the capability to supply appropriate ''wet lab'' space. Relationships with markets are especially important in assisting firms to find expert commercial partners (Norton, 2000;Zook, 2000;Cooke, 2002a,b); Powell et al, 2002). In Section 3 efforts will be made to characterise the eight bioincubators in the Bio-Link study according to the range of services they supply and the direct and indirect nature of those services.…”
Section: A Model Of the Kvc In Life Sciences And The Role Of Incubationmentioning
confidence: 99%